Vygotsky's criticism of fascism in German psychology of the 1930s: political, socio-psychological and personal contexts - Vladimir S. Sobkin; Gleb D. Emelin (Lomonosov Moscow State University, 2023)
Background. This study discusses one of the last Vygotsky`s works - the fourth chapter in «Fascism in Psychoneurology» bulletin (1934). Motivation of the author to write this text is analyzed in the broad context of sociopolitical and personal aspects of his life: general growth of sociopsychological tension, repressions that touched Vygotsky`s family in 1930s, personally significant Jewish question and antisemitism in nazi Germany. In addition, joint letter from R.N. Vygodskaya and L.S. Vygotsky to D.I. Vygodsky published for the first time. This letter mentioned the arrest of Vygotsky`s cousin L.I. Vygodsky. Objective. The aim of the study was to reconstruct personal meanings and circumstances of L.S. Vygotsky in writing a chapter for «Fascism in Psychoneurology» bulletin. Methods. Elements of source analysis, search and analysis of archival documents, theoretical analysis of literature on L.S. Vygotsky`s biography. Results. The analysis showed that Vygotsky and Luria`s criticism of Fascism in psychology is built around several topics: criticism of the basic anthropological idea of the Third Reich about the predestination of human development depending on «blood and race»; an analysis of the process of politicization and ideologization of science, exemplified by the concept of «Integrationstypologie» introduced by E.R. Jaensch, which Vygotsky criticizes; political self-defense of Soviet scientists against possible persecution; the issue of national self-determination of Soviet Jewish scientists. Conclusion. Authors of this article suggested that this work may be seen not only as a scientific criticism and assertion of humanistic values in psychology but also as an act of political self-defense from sanctions and persecution that took place during the second half of the 1930s.